Effects of Black Jade on Osteogenic Differentiation of Adipose Derived Stem Cells under Benzopyrene - Yoonjin Park; Gyeong Hee Shin; Gyo Sik Jin; Sungbae Jin; Boyong Kim; Seung Gwan Lee (Applied Sciences, 2021)
Jade, a popular gemstone symbolizing beauty, grace, and longevity, is known to improve blood circulation; however, scientific research evidence is still lacking. The effect of black jade extract on the expression levels of apoptotic and osteogenic genes was validated using qPCR and flow cytometry. In combination with the use of a fluorescence microscope, osteogenic differentiation and the stained osteocytes count were analyzed. Under the pressure of benzo(a)pyrene, dermal cell apoptosis was accelerated and the osteogenic differentiation of adipose-derived stem cells (ASCs) was suppressed; but black jade extract counteracted the effects. Through an anti-apoptotic mechanism, the extract suppressed the expression of apoptotic proteins Bax and cytochrome C to 9 and 4.8 times, respectively, compared to that in dermal cells exposed to benzo(a)pyrene. During osteogenic differentiation of ASCs, the extract enhanced their differentiation despite being exposed to benzo(a)pyrene, and the relative levels of the osteoblast differentiation markers osteoponin, osteocalcin, and sclerostin were 1.87, 2.54, and 3.9 times higher, respectively, than those in the conditioned medium by benzo(a)pyrene. These effects of the extract indicate that black jade extract is very useful when applied as a functional biomaterial.